1999
DOI: 10.1177/002215549904701203
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Separated Mouse Mammary Luminal Epithelial and Myoepithelial Cells Cultured on EHS Matrix Analyzed by Indirect Immunofluorescence of Cytoskeletal Antigens

Abstract: SUMMARYWe have previously demonstrated that purified virgin mouse mammary luminal epithelial and myoepithelial cells promiscuously express cell type-specific cytokeratins when they are cloned in vitro. Changes in cytokeratin expression may be indicators of the loss or change of the differentiated identity of a cell. To investigate the factors that may be responsible for the maintenance of differentiated cellular identity, specifically cell-cell and cell-matrix interactions, we cloned flow-sorted mouse mammary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
3
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 33 publications
(58 reference statements)
6
51
3
1
Order By: Relevance
“…The morphology and ratios of the clone types were consistent with the type A-D classification found when unsorted primary mammary epithelial cells were cloned [8,15]. Identical clone types and ratios of types A-D were observed following growth of SP and non-SP preparations.…”
Section: In Vitro and In Vivo Differentiation Of Sp Cellssupporting
confidence: 78%
See 1 more Smart Citation
“…The morphology and ratios of the clone types were consistent with the type A-D classification found when unsorted primary mammary epithelial cells were cloned [8,15]. Identical clone types and ratios of types A-D were observed following growth of SP and non-SP preparations.…”
Section: In Vitro and In Vivo Differentiation Of Sp Cellssupporting
confidence: 78%
“…Double immunofluorescence staining of clones, using the antibodies LE61 and LP2K (anticytokeratin 18 and anticytokeratin 19, respectively; in vivo markers of mammary luminal epithelial cells) and LLOO2 (anticytokeratin 14; a marker of mammary myoepithelial cells) [8,15], demonstrated that SP-derived and non-SP-derived clones had identical staining patterns. All were uniformly strongly positive for cytokeratin 18, and most cells within clones also double stained for cytokeratin 14.…”
Section: In Vitro and In Vivo Differentiation Of Sp Cellsmentioning
confidence: 99%
“…Smalley et al demonstrated that sorted mouse myoepithelial cells give rise only to a single type of clones, whereas sorted luminal epithelial cells give rise to three morphologically distinct clonal types which show progressive acquisition of myoepithelial markers (34,37). In another study, albeit not using cell separation protocols, Kao et al defined two breast epithelial cell types by clonal dilution culture.…”
Section: The Origin Of Myoepithelial Progenitor Cellsmentioning
confidence: 99%
“…Isolation of adipocytes and epithelial cells was performed as previously described ( 17,18 ). Briefl y, thoracic mammary glands were dissected from virgin female mice (three glands for each preparation).…”
Section: Isolation Of Adipocytes and Mammary Epithelial Cellsmentioning
confidence: 99%